Web Series as Digital Brand - R D Santy; D D Anwar (International Journal of Research and Applied Technology (INJURATECH), 2021)
The purpose of this research is to explain the role of the Web Series in discussing and delivering messages to audiences about the "value" of the product, where the web series published on digital media such as Youtube that becomes the attractive promotional strategies for the consumers. This research used a qualitative method with a descriptive approach that explains the promotion strategy and brand engagement through the web series that became a new content marketing campaign. The results of this study are the increased proximity between customers and brand as well as the increased understanding brand which leads to brand awareness because attractive promotional strategies can attract the attention of consumers. The use of web series to build engagement with customers also has its own added value, where the web series can also be used as a product campaign such as Ax Indonesia, which released a Web Series Axelerate the series: Kostan AX/3 that is in conjunction with the launch of their new product, Pomade, and Facial Wash. This study concludes that the approach to consumers must be adjusted to the characteristics of consumers themselves so that messages can be conveyed more effectively and on target.